Homoeopathy for Upper Respiratory Tract Infection in Children: A Narrative Review of Research Evidence - Dutta, Abhijit; Sehrawat, Nisha (Homœopathic Links, 2020)
Background Upper respiratory tract infection (URTI) is one of the leading causes of morbidity worldwide, especially in the paediatric age group. Conventional medications have a minimal role in treating and preventing those diseases and an alternative for this is warranted. In this regard, homoeopathy can be a proper consideration, but the comparative effect and safety need critical evaluation.Methods To evaluate the role of homoeopathic treatment in URTI, particularly in children, we conducted a comprehensive search in PubMed, Core-Hom, Cochrane library and Cam-quest database. All the relevant studies were included for a critical review.Results One-hundred forty articles were found in a preliminary search, and for review, we included 17 studies related to URTI in paediatric age group. All the studies were very diverse in the methodology, type of homoeopathy used and outcome measurement. Different types of homoeopathy in terms of individualised, complex syrup and home-medication were used in studies. Fourteen studies reported the role of homoeopathy in reducing the severity of symptoms, efficacy beyond placebo, superiority or non-inferiority over conventional medications, in lowering the consumption of antibiotics and as prophylaxis. On the other hand, three studies found little or no effect in reducing symptoms or number of visits.Conclusions Homoeopathic treatment improves the symptoms and reduces the severity of URTI in the paediatric age group. It can be an effective and safe way of treatment for reducing the burden of the disease, thus improving the quality of life. Owing to the diversity among the studies, more high-quality trials with focused questions are needed for further conclusion.
Keywords: homoeopathy; paediatric; URTI; quality of life; narrative review